WORK RELATED STRESS AND EMPLOYEES’ COMMITMENT: A CASE STUDY OF A PRIVATE UNIVERSITY - SANDRA AJAYI OSAMA; EVELYN UMEMEZIA (Annals of the University of Petrosani: Economics)
The paper investigates the impact of work related stress on employees’ commitment. Its’ objective is to determine if there is a relationship between work stress and employees' commitment to the investigated organization. The research, which is crosssectional, made use of questionnaires to elicit data from 162 staff of Benson Idahosa University. These data were analyzed using the regression statistical technique. The analyses revealed that work stress was negatively correlated to affective, continuance, and normative commitment. The findings underscore the importance of reducing and managing work overload, lack of autonomy and role conflict which are antecedents of work related stress as a way of improving employees’ commitment to the organization.